"As estrelas eram terrenas": antropologia do clima, da iconografia e das constelações Ticuna - Faulhaber, Priscila (Revista de Antropologia, 2004)
The anthropology of weather includes the study of the significance of astronomical and atmospheric phenomena within indigenous myths and rituals as well as of the importance of representations of these phenomena for the social practices of indigenous people. Among the Ticuna of Upper Solimões (Brazil) the celestial bodies depicted in the iconography of artifacts used in the Ticuna puberty festival can be related to some aspects of this people's mythology and cosmovision, as expressed in ritual chants and speeches. This relation is translated into expectations regarding the inter-relationships between the annual movement of the stars in the sky and the influence of the rainy and dry seasons for survival activities. The identification of groups of celestial bodies visualized by the Ticuna allows us to establish their correlations with the conventionally reconized constellations.